2019
DOI: 10.1080/09537104.2019.1572880
|View full text |Cite
|
Sign up to set email alerts
|

Very-low-dose twice-daily aspirin maintains platelet inhibition and improves haemostasis during dual-antiplatelet therapy for acute coronary syndrome

Abstract: Higher aspirin doses may be inferior in ticagrelor-treated acute coronary syndrome (ACS) patients and reducing bleeding risk whilst maintaining antithrombotic benefits could improve outcomes. We characterized the pharmacodynamics of a novel dual-antiplatelet-therapy regimen consisting of verylow-dose twice-daily (BD) aspirin with standard-dose ticagrelor. A total of 20 ticagrelor-treated ACS patients entered a randomized crossover to take aspirin 20 mg BD (12-hourly) during one 14-day period and 75 mg once-dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…Upon activation, several key processes occur. First, arachidonic acid is converted to thromboxane A 2 , a potent pro-aggregatory and vasoconstrictive factor [ 12 ]. Second, platelets degranulate.…”
Section: Mechanistic Relationships Between Inflammation and Thrombosimentioning
confidence: 99%
“…Upon activation, several key processes occur. First, arachidonic acid is converted to thromboxane A 2 , a potent pro-aggregatory and vasoconstrictive factor [ 12 ]. Second, platelets degranulate.…”
Section: Mechanistic Relationships Between Inflammation and Thrombosimentioning
confidence: 99%
“…Similarly, several independent studies have consistently shown the superior biochemical efficacy of a strategy based on shortening the dosing interval versus a strategy of maintaining or increasing the once daily dose of aspirin in patients with type-2 diabetes mellitus (Spectre et al, 2011; Rocca et al, 2012; Bethel et al, 2016), undergoing CABG (Paikin et al, 2015; Cavalca et al, 2017), or presenting with an acute coronary syndrome (Parker et al, 2019).…”
Section: Serum Txb2 As a Validated Index Of Platelet Cox-1 Activitymentioning
confidence: 99%
“…Therefore, lower-than-standard dose aspirin could hypothetically reduce the risk of bleeding and associated complications of COX-2 inhibition while maintaining anti-thrombotic efficacy. A recent study (WIL-LOW ACS) characterised a novel regimen of very-low-dose aspirin (20 mg BD) plus ticagrelor over two weeks in 20 patients with recent ACS [188]. Compared with standard-dose aspirin (75 mg OD) plus ticagrelor, the novel regimen reduced peak COX-1 inhibition, which was associated with a significant reduction in bleeding time and without a significant difference in arachidonic acid-induced platelet aggregation.…”
Section: Ticagrelor Monotherapy Studies and Studies Of Lower Dose Aspirinmentioning
confidence: 99%